UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PEMBERIAN TUGAS (RESITASI) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI TATA KRAMA, SOPAN SANTUN DAN RASA MALU DI KELAS IX-4 SMP NEGERI 29 MEDAN TAHUN AJARAN 2019/2020 - Suhartati Suhartati (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
The research instrument used was a test of student learning outcomes. Based on the results of the study, after being given action in the first cycle, classical learning mastery was obtained by 25%, while in the second learning outcome test, classical learning mastery was obtained by 68.75% or an increase of 43.75% from the first cycle, and on the test the results learning III obtained classical learning completeness of 87.50% or an increase of 18.75% from cycle II. So that the assignment method approach (recitation) on the material of manners, manners and shame can improve student learning outcomes in Islamic religious education in class IX-4 SMP Negeri 29 Medan